Physiological and Yield Responses of Some Selected Rapeseed/Mustard Genotypes to Salinity Stress (Bangladesh Agronomy Journal, 2021)
An experiment on rapeseed/mustard genotypes was conducted during 2019-2020 rabi season in vinyl house of Plant Physiology Division of Bangladesh Agricultural Research Institute (BARI), Gazipur to find out the salt-tolerant genotypes based on the responses of their physiological parameters and yield. Five selected rapeseed/ mustard genotypes (V1= Jun-536, V2 = BJDH-12, V3 = BD-10115, V4 = BARI Sarisha-14, V5 = BD-6950) were tested at three salinity levels (S0= 0, S1= 5 and S2=10 dS m-1). Irrespective of the genotypes, salinity stress showed a negative effect on the measured physiological parameters as well as seed yield. Leaf chlorophyll contents, leaf area, leaf photosynthetic rate and total dry matter (TDM) were reduced due to salinity stress which ultimately affected seed yield irrespective of the genotypes. However, these parameters were less affected by the salinity in V1 and V2 genotypes compared to others. Sodium and potassium ion contents and their ratios (K+/Na+) in leaf tissues were significantly affected by salinity stress. Among the genotypes, V1 and V2 showed higher K+/Na+ ratios in leaf under both the salinity treatments, and that phenomenon indicated their higher tolerance to salinity than the other genotypes. Catalase (CAT), Peroxidase (POD) activity and Malondialdehyde (MDA) content of the genotypes increased due to salinity stress with variability among the genotypes. The higher CAT and POD activity with lower MDA content was found in V1 and V2 genotypes which indicated their better salt tolerance ability compared to others. These genotypes also showed higher seed yield under both the salinity levels (5 and 10 dS m-1) compared to other genotypes. Based on the responses of physiological parameters and seed yield to salinity, the genotypes Jun-536(V1) and BJDH-12(V2) could be considered relatively tolerant to salinity stress.Bangladesh Agron. J. 2021, 24(1): 43-55